OPTIMIZATION OF SCREEN PRINTED REFERENCE ELECTRODE BASED ON CHARGE BALANCE AND POLY (BUTYL ACRYLATE) PHOTOCURABLE MEBRANE - S. Alva; L. Y. Heng; M. Ahmad (Universitas Mercu Buana, 2016)
This research focus on transforming the traditional design of reference electrode into all-solid-state reference electrode front-end using Ag/AgCl screen- printed electrodes. By replacing the internal reference solution of a traditional reference electrode by a solid photocurable membrane, an all-solid-state reference electrode can be achieved. The solid-state screen-printed reference electrode was designed using a photocurable acrylic film containing immobilized sodium tetrakis [3,5-bis(trifluoromethyl)phenyl] borate (NaTFPB) and trimethylocthylammonium chloride (TOMA-Cl). An optimum ratio of NaTFPB:TOMA-Cl = 1:1 produced a stable reference electrode. In the anions interference studies, all anions i.e. NO3-, Cl-, Br- and SO42- does not give effect to the SPRE except perchlorate anions. The all-solid-state reference electrodes was applied to the detection of potassium ions and ammonium ions. Validation of the all-screen-printed reference electrode was performed with reference electrode standard gel type. The validation results showed that all-solid-state screen-printed reference electrode demonstrated performance that was comparable to standard reference electrode.